Natural composites integrated with fire retardants: A review. (2020) - Parkunam, N.; Saravanan, S.; Navaneethakrishnan, G.; Aravindh, M.; Chidambaranathan, P.; Chrishore Thomas, G.; Kamaraj, R.
Abstract: The ultra modern study aims in learning about the mechanical and thermal properties of the particle and fiber reinforced polymer composites incorporated with fire retardants. The natural fibers are reinforced with base matrixes. The study also compares different types of fire retardants for the best one and also the optimum composition for the fire retardants in the composite material. From the result it was found that epoxy composite has great mechanical property and thermal stability. The fire retardants are added with composite to improve the thermal stability. It shows that boron compound have superior thermal stability and valuable smoke suspension.